Analisis Butir Soal Latihan pada Buku al-Naḥw al-Wāḍīḥ untuk Siswa Madrasah Aliyah - Bagusradityo Aryobimo (Universitas Negeri Jakarta, 2021)
Practice questions are the main part of every textbook, especially to evaluate and measure students’ abilities and skills. One of the books that are often used as a textbook by various madrasas and Islamic boarding schools on learning naḥwu for beginners is the al-Naḥw al-Wāḍīḥ. Unfortunately, this book has not determined the quality in the validity of practice for the lesson, because it was written by an Arabic native speaker. So, the target of this book is not for non-native Arabic speakers. This study uses a mixed method of qualitative and quantitative to describe a more complete picture of item analysis. The purpose of this study was to determine the quality of practice questions in the al-Naḥw al-Wāḍīḥ book in terms of validity, reliability, level of difficulty, and discriminating power. The results obtained are, (1) 93% of the exercise sample is under content validity; (2) from the results of the ANOVA test of two exercise samples, this test is quite reliable; (3) the difficulty level of the sample practice questions on naḥwu is fairly easy; (4) the discriminating power of the nahwu sample is sufficient. Thus, the analysis of practice questions in al-Naḥw al-Wāḍīḥ is sufficient to measure students’ abilities.